The endoplasmic reticulum-associated protein, OS-9, behaves as a lectin in targeting the immature calcium-sensing receptor - Ward, B.; Rea, S.; Magno, A.; Pedersen, B.; Brown, S.; Mullin, S.; Arulpragasam, Ajanthy; Ingley, E.; Conigrave, A.; Ratajczak, T. (John Wiley & Sons, Inc., 2017)
The mechanisms responsible for the processing and quality control of the calcium-sensing receptor (CaSR) in the endoplasmic reticulum (ER) are largely unknown. In a yeast two-hybrid screen of the CaSR C-terminal tail (residues 865-1078), we identified osteosarcoma-9 (OS-9) protein as a binding partner. OS-9 is an ER-resident lectin that targets misfolded glycoproteins to the ER-associated degradation (ERAD) pathway through recognition of specific N-glycans by its mannose-6-phosphate receptor homology (MRH) domain. We show by confocal microscopy that the CaSR and OS-9 co-localize in the ER in COS-1 cells. In immunoprecipitation studies with co-expressed OS-9 and CaSR, OS-9 specifically bound the immature form of wild-type CaSR in the ER. OS-9 also bound the immature forms of a CaSR C-terminal deletion mutant and a C677A mutant that remains trapped in the ER, although binding to neither mutant was favored over wild-type receptor. OS-9 binding to immature CaSR required the MRH domain of OS-9 indicating that OS-9 acts as a lectin most likely to target misfolded CaSR to ERAD. Our results also identify two distinct binding interactions between OS-9 and the CaSR, one involving both C-terminal domains of the two proteins and the other involving both N-terminal domains. This suggests the possibility of more than one functional interaction between OS-9 and the CaSR. When we investigated the functional consequences of altered OS-9 expression, neither knockdown nor overexpression of OS-9 was found to have a significant effect on CaSR cell surface expression or CaSR-mediated ERK1/2 phosphorylation.